2017
DOI: 10.1021/acs.jpcc.7b09674
|View full text |Cite
|
Sign up to set email alerts
|

Surface Structure of TiO2 Rutile (011) Exposed to Liquid Water

Abstract: The rutile TiO2(011) surface exhibits a (2 × 1) reconstruction when prepared by standard techniques in ultrahigh vacuum (UHV). Here we report that a restructuring occurs upon exposing the surface to liquid water at room temperature. The experiment was performed in a dedicated UHV system, equipped for direct and clean transfer of samples between UHV and liquid environment. After exposure to liquid water, an overlayer with a (2 × 1) symmetry was observed containing two dissociated water molecules per unit cell. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 37 publications
(56 reference statements)
4
47
0
Order By: Relevance
“…Desorption of TiOF 2 points to strong Ti-F covalent bonding of F to the surface during the HF zipping, which may indirectly explain the observed surface reconstruction under newly formed HBC molecules. Adsorbates strongly interacting with the surface are known to induce changes in rutile titania reconstructions, as previously reported for (110) (39) and (011) (40,41) faces. Recent work by Balajka et al (41) reported a water-induced reconstruction of a rutile (011) surface to form a bulk-terminated (1×1) face covered with a hydroxyl group overlayer forming (2×1) reconstruction.…”
supporting
confidence: 66%
“…Desorption of TiOF 2 points to strong Ti-F covalent bonding of F to the surface during the HF zipping, which may indirectly explain the observed surface reconstruction under newly formed HBC molecules. Adsorbates strongly interacting with the surface are known to induce changes in rutile titania reconstructions, as previously reported for (110) (39) and (011) (40,41) faces. Recent work by Balajka et al (41) reported a water-induced reconstruction of a rutile (011) surface to form a bulk-terminated (1×1) face covered with a hydroxyl group overlayer forming (2×1) reconstruction.…”
supporting
confidence: 66%
“…Besides the influence on physical and chemical properties, an overlayer of water was recently proved to change the reconstruction of the technologically relevant TiO 2 rutile (011) surface. 1 Therefore, the adsorption mechanism of water on metal oxide surfaces is a key aspect to be investigated in order to control and improve processes that take place at the solid/liquid interface.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, water mono or multilayer adsorption may alter the surface electronic properties and work function, as well as the surface energy leading to different reconstructions than in ultra-high vacuum conditions. 3 Recently, it was even reported to affect the trapping dynamics of photogenerated charge carriers in TiO 2 . 4 , 5 …”
Section: Introductionmentioning
confidence: 99%